Perbandingan Hasil Pengoksidan Elektrokimia Etanol dalam Larutan Alkali yang Menggunakan Elektrod Platinum-Polivinilklorida (Pt-PVC) dan Kepingan Logam Pt = Comparison of Electrooxidation Yield of Ethanol in Alkaline Medium using Platinum-Polyvinyl chloride (Pt-PVC) and Pt Metal Foil Electrodes (Universiti Kebangsaan Malaysia, 2007)
A modification of platinum-polyvinyl chloride (Pt-PVC) electrode for the electrooxidation of ethanol in alkaline solution has been investigated. Pt-PVC electrode was prepared by mixed together platinum metal powder with PVC (95:5 w/w), homogenized, added with tetrahydrofuran to dissolved the dried, put into 1 cm diameter mould and press at 10 ton/cm2. Studies on electrochemicals behavior for Pt-PVC electrode were carried out using cyclic voltammetry and chronocoulometry modes. The higher current density for hydroxide adsorption peak were recorded, 0.25 mA/cm2 and 85 mA/cm2 respectively when Pt-PVC electrode was used compared to Pt electrode. This indicates that Pt-PVC electrode gives better conductivity and electrochemical behavior to electrooxidation of ethanol in KOH compared to Pt electrode. Result obtained shows the used of Pt-PVC electrode for electrooxidation of 0.25 M ethanol in 1.0 M KOH supporting electrolyte increased the percentage of acetic acid produced compared to Pt electrode.